2004
DOI: 10.1038/sj.onc.1207534
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial membrane permeabilization in apoptosis and cancer

Abstract: The release of proteins from the intermembrane space of mitochondria is one of the pivotal events in the apoptotic process, which can lead to the activation of caspases and the ultimate demise of the cell. How these proteins exit the mitochondria is still a matter of intense debate. Here, we discuss the possible mechanisms behind the release of apoptogenic proteins, the ways in which cancer cells subvert these mechanisms, and the therapeutic regimens that aim to promote the timely loss of integrity of the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
141
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(155 citation statements)
references
References 128 publications
9
141
1
4
Order By: Relevance
“…A large number of such assays have been used and most of them are reliable. However, (1) cells having sub-G 1 DNA content have been assumed to be apoptotic (Chan et al, 2003;Jazirehi et al, 2003), but various types of cell fragments also may have a sub-G 1 DNA content, and we demonstrate herein that three types of necrotic cell preparations have large numbers of cells with sub-G 1 DNA; (2) similarly, although apoptotic cells lose mitochondrial membrane potential (Darzynkiewicz et al, 2001) and although the mitochondrial membrane is a major focus of apoptotic pathways (Green, 2003;Henry-Mowatt et al, 2004), we show that necrotic cells also lose mitochondrial membrane potential; (3) subcellular fragments can potentially interfere with assays such as annexin V staining. Apoptosis and other types of cell death usually generate subcellular fragments, and these may be mistaken for apoptotic cells; (4) cell damage owing to irradiation causes an increase in nonspecific Ab binding (to viable, nonapoptotic cells), which can lead to false conclusions regarding Ab specificity if negative control Abs are not tested; and (5) Ab binding can induce tight aggregation of cells, especially if a secondary Ab is included.…”
supporting
confidence: 57%
“…A large number of such assays have been used and most of them are reliable. However, (1) cells having sub-G 1 DNA content have been assumed to be apoptotic (Chan et al, 2003;Jazirehi et al, 2003), but various types of cell fragments also may have a sub-G 1 DNA content, and we demonstrate herein that three types of necrotic cell preparations have large numbers of cells with sub-G 1 DNA; (2) similarly, although apoptotic cells lose mitochondrial membrane potential (Darzynkiewicz et al, 2001) and although the mitochondrial membrane is a major focus of apoptotic pathways (Green, 2003;Henry-Mowatt et al, 2004), we show that necrotic cells also lose mitochondrial membrane potential; (3) subcellular fragments can potentially interfere with assays such as annexin V staining. Apoptosis and other types of cell death usually generate subcellular fragments, and these may be mistaken for apoptotic cells; (4) cell damage owing to irradiation causes an increase in nonspecific Ab binding (to viable, nonapoptotic cells), which can lead to false conclusions regarding Ab specificity if negative control Abs are not tested; and (5) Ab binding can induce tight aggregation of cells, especially if a secondary Ab is included.…”
supporting
confidence: 57%
“…The mechanisms regulating the release of specific mitochondrial proteins during cell death are not completely understood (Donovan and Cotter, 2004;Henry-Mowatt et al, 2004;Saelens et al, 2004). Our data showed that A3D8 treatment induced loss of DCm and AIF release from mitochondria without cytochrome c release.…”
Section: Cd44-induced Cell Death In Erythroleukemia Cellsmentioning
confidence: 71%
“…Key events in classic apoptosis as well as in other forms of cell death are the disruption of mitochondrial function and the release of apoptogenic proteins from the intermembrane space (IMS) of mitochondria (Henry-Mowatt et al, 2004;Saelens et al, 2004). Although the process of the mitochondrial outer membrane permeabilization (MOMP) is mainly controlled by the members of the Bcl-2 family, the exact mechanisms responsible of this process remain controversial (Donovan and Cotter, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Two major apoptotic signaling pathways have been identified: the death receptor-mediated (extrinsic) pathway and the mitochondrial (intrinsic) pathway (Ashkenazi and Dixit, 1998;Kroemer and Reed, 2000;Gupta, 2003;Debatin and Krammer, 2004;Henry-Mowatt et al, 2004). The relative contribution of death receptor versus mitochondrial pathways in apoptosis reflects the existence of two different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Bax and Bak proteins contain three BH domains and are localized in the cytosol and mitochondrial membrane. Other proapoptotic proteins containing a single BH domain serve either to inactivate antiapoptotic proteins or activate Bax or Bak (Gupta, 2003;Henry-Mowatt et al, 2004;Saelens et al, 2004). Bad is a BH3-only protein that links survival signals to the mitochondrial cell death machinery (Zha et al, 1996;Korsmeyer et al, 1999;Datta et al, 2002).…”
Section: Introductionmentioning
confidence: 99%